Effectiveness of Community Smoking Prevention Education in Enhancing Adolescent’s Knowledge in Banyuwangi Indonesia - Azimatul Karimah; Soetjipto; Izzatul Fithriyah; Sheila Maryam Gautama; Agustina Sjenny; Adila Taufik Syamlan; Adhilah, Nindy; Dina Faizatur Rahmah; Williana Suwirman; Virzi Aliyyah Rahma; Teisha Jediya Videlia Marantika; Rifat Nurwita Kusumaningtyas; Andyani Pratiwi; Rizka Solehah (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: Tobacco consumption increases the risk of chronic diseases and death. In Indonesia, the prevalence of active smokers is estimated to reach 27% of the population, or 70 million people, with 7.4% of them aged 10-18 years. The aim of this study is to assess the effectiveness of community smoking prevention education in enhancing adolescent knowledge in Banyuwangi, Indonesia. Methods: This study used a quasi-experimental research design with a pre- and post-test one-group approach. In this study, we employed total sampling as our sampling technique. The samples were students of class X SMA Negeri 1 Giri Banyuwangi, aged 14-16 years old. The intervention includes a presentation on long-term health consequences, the risk of addiction, and the adverse effects of smoking. Psychiatrists led our intervention, sharing general knowledge about smoking behavior and its risk for health outcomes. Results: The study ultimately employed a final sample of 49 participants. The paired t-test increased from the pre-test (53.47) to the post-test (63.47) score average. The standard deviation for the pre-test and post-test is 14.513. Eventually, the standard error mean for the pre-test and post-test is 2.073. The average learning outcome in the pre-test (53.47) is less than that of the post-test (63.47), and the p-value is 0.000, which is less than 0.05. Conclusion: The study’s results indicated that prevention education had a significant impact on increasing adolescents’ knowledge about smoking (p = 0.000). Regular prevention programs could further enhance adolescents’ understanding of the topic.